Neurofeedback Against Binge Eating: A Randomized Controlled Trial in a Female Subclinical Threshold Sample. (27th April 2016) - Schmidt, Jennifer; Martin, Alexandra
Abstract: Brain‐directed treatment techniques, such as neurofeedback, have recently been proposed as adjuncts in the treatment of eating disorders to improve therapeutic outcomes. In line with this recommendation, a cue exposure EEG‐neurofeedback protocol was developed. The present study aimed at the evaluation of the specific efficacy of neurofeedback to reduce subjective binge eating in a female subthreshold sample. A total of 75 subjects were randomized to EEG‐neurofeedback, mental imagery with a comparable treatment set‐up or a waitlist group. At post‐treatment, only EEG‐neurofeedback led to a reduced frequency of binge eating ( p  = .015, g  = 0.65). The effects remained stable to a 3‐month follow‐up. EEG‐neurofeedback further showed particular beneficial effects on perceived stress and dietary self‐efficacy. Differences in outcomes did not arise from divergent treatment expectations. Because EEG‐neurofeedback showed a specific efficacy, it may be a promising brain‐directed approach that should be tested as a treatment adjunct in clinical groups with binge eating. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.